2011
DOI: 10.1117/12.878043
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy micro-CT imaging for differentiation of iodine- and gold-based nanoparticles

Abstract: Spectral CT imaging is expected to play a major role in the diagnostic arena as it provides material decomposition on an elemental basis. One fascinating possibility is the ability to discriminate multiple contrast agents targeting different biological sites. We investigate the feasibility of dual energy micro-CT for discrimination of iodine (I) and gold (Au) contrast agents when simultaneously present in the body. Simulations and experiments were performed to measure the CT enhancement for I and Au over a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…For this reason, the optimal sensitivity matrix was calibrated using low to intermediate concentrations of I and Au (0, 2, 4, 6 mg/mL) which were presumed to be least affected by beam hardening. In practice, calibrating the sensitivities with higher concentrations yields uniformly lower sensitivities for I and Au at 40 and 80 kVp as documented in (Badea et al , 2011). As a consequence of the choice to optimize the sensitivity matrix for low to intermediate concentrations, the sensitivity matrix derived here is better conditioned than the sensitivity matrix previously derived, improving the accuracy in separating I and Au, particularly near the limits of detectability of the two materials.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For this reason, the optimal sensitivity matrix was calibrated using low to intermediate concentrations of I and Au (0, 2, 4, 6 mg/mL) which were presumed to be least affected by beam hardening. In practice, calibrating the sensitivities with higher concentrations yields uniformly lower sensitivities for I and Au at 40 and 80 kVp as documented in (Badea et al , 2011). As a consequence of the choice to optimize the sensitivity matrix for low to intermediate concentrations, the sensitivity matrix derived here is better conditioned than the sensitivity matrix previously derived, improving the accuracy in separating I and Au, particularly near the limits of detectability of the two materials.…”
Section: Discussionmentioning
confidence: 90%
“…In a recent study we performed both simulations and experimental validation in phantoms to determine the optimal scanning energies for the separation of Au and I using our micro-CT system (Badea et al , 2011). Our work has shown that micro-CT imaging at 40 and 80 kVp provides the best decomposition results in terms of accuracy and contrast.…”
Section: Methodsmentioning
confidence: 99%
“…Multi-energy CT offers better characterisation of materials, image reconstruction optimisation, and experimental iodine-, bismuthand gold-labelled nanoparticle contrast agents for tagging of disease processes in vivo e.g. fibrin [7], macrophages [8] and colon cancer [9].…”
Section: Introductionmentioning
confidence: 99%
“…For the dual source micro-CT system, 40 kVp is the lowest voltage allowed by the micro-CT system’s x-ray generator. This voltage provides minimum enhancement, while values in the range of 70 or 80 kVp provide maximum enhancement when imaging iodine solutions[17]. Bilateral filtering was also applied.…”
Section: Methodsmentioning
confidence: 99%